Penguatan Kapasitas Kader melalui Edukasi Video Makanan Pendamping ASI di Desa Dangdeur, Kecamatan Jayanti, Kabupaten Tangerang - Sandra Hakiem Afrizal; Marina Indriasari; Romi Romi (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
In 2021, the stunting rate in Dangdeur Village was still relatively high and is expected to decrease by 2024. Dangdeur Village, located in Jayanti Sub-district, Tangerang Regency, is one of the urban areas in Banten Province. Currently, the village has one main Posyandu (integrated health service post) with 10 satellite Posyandu units supported by 25 active cadres. The role of these cadres is crucial in efforts to reduce stunting rates. The method used in this program involved educating cadres through the screening of an educational video about complementary feeding (MPASI). This activity was conducted in August 2024. Before and after the video screening, cadres were given a series of questions to assess their knowledge levels. A total of 25 active cadres participated in the program, and the average knowledge score increased from 63 (Pre-test) to 78 (Post-test). It is hoped that this community service program will help reduce the prevalence of stunting among children in Dangdeur Village and can be implemented in other regions across Indonesia.